Tingkat Moderasi Beragama Mahasiswa Institut Agama Islam Negeri Sorong - fitri, Nurfitriani; Sella Nofriska Sudrimo (LPPM IAIN Sorong, 2024)
This research uses mixed methods, namely a combination of quantitative and qualitative research techniques, with the aim of producing a more comprehensive picture of the Level of Religious Moderation of IAIN Sorong Students. The methodology used was simple random sampling, 170 students were taken from all faculties to be used as samples for this research. The research results show that IAIN Sorong students have a good level of religious moderation, namely not too extreme to the left (liberal) and not too extreme to the right (fanatic, radical and anarchist). The indicators of national commitment, accommodating to local culture, anti-radicalism and violence range between 60% and are in the high category. Meanwhile, the percentage tolerance indicator is 45%, and is still relatively low. From the research results, it can be concluded that it is important to maintain and further improve the understanding and application of the concept of religious moderation. Students in the future will act as catalysts for moderate diversity in a pluralistic society, so it is the collective task of the entire campus academic community to continue to socialize the concept of religious moderation again, in order to create a harmonious life amidst the diversity of Papuan society.